Older and Wiser? The Need to Reexamine the Impact of Health Professionals Age and Experience on Competency-Based Practices - Jing Xu PhD, MHA; Kristen Hicks-Roof PhD, RDN, LDN, FAND; Chloe E. Bailey MHA, BHA; Hanadi Y. Hamadi PhD, MHA (SAGE Publishing, 2021)
Introduction Delivery of healthcare services makes up a complex system and it requires providers to be competent and to be able to integrate each of the institute of medicine's (IOM) 5 core competencies into practice. However, healthcare providers are challenged with the task to be able to understand and apply the IOM core competencies into practice. Objective The purpose of the study was to examine the factors that influence health professional's likelihood of accomplishing the IOM core competencies. Methods A cross-sectional study design was used to administer a validated online survey to health providers. This survey was distributed to physicians, nursing professionals, specialists, and allied healthcare professionals. The final sample included 3,940 participants who completed the survey. Results The study findings show that younger health professionals more consistently practice daily competencies than their older counterparts, especially in the use of evidence-based practice, informatics, and working in interdisciplinary teams. Less experienced health professionals more consistently applied quality improvement methods but less consistently used evidence-based practice compared to their more experienced counterparts. Conclusion There is a need to understand how health professionals' age and experience impact their engagement with IOM's core competencies. This study highlights the need for educational resources on the competencies to be tailored to health providers' age and experience.